Effect of different drying methods on retention of colour, total phenolic content, flavonoid content and antioxidant activity in Pereskia bleo leaves - Nurain Nabilah Zulkipli,; Iman Nur Sabrina Norasmadi,; Suhaizan Lob,; Wan Zaliha Wan Sembok,; Nurud Iliani Suhaimi,; Aidilla Mubarak, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Pereskia bleo, a widely cultivated plant known for its medicinal applications, contains abundant phytochemicals, including phenolics and flavonoids, predominantly in its leaves. The drying process, a standard practice for enhancing the shelf life, could affect the bioactive compounds within the leaves. Therefore, this study aims to evaluate the impact of various drying methods on the colour, total phenolic content, flavonoid content, and antioxidant activity of P. bleo leaves. The tested drying methods include shade, oven, microwave, and freeze-drying. The colour of fresh and dried leaves was assessed using a Minolta chromameter. The total phenolic content (TPC) and total flavonoid content (TFC) of the P. bleo leaves extracts were determined using the Folin-Ciocalteu’s and aluminium chloride colourimetric assay, respectively. Antioxidant capacities were analysed with DPPH radical scavenging and ferric-reducing antioxidant power assay (FRAP). The results showed that microwave drying has significantly less impact than the other drying methods on the colour attributes of the leaves (p<0.05). Notably, microwave-dried P. bleo leaves demonstrated significantly higher TPC (77.31 ± 0.70 mg GAE/g dry extract) and TFC (35.79 ± 1.34 mg QE/g dry extract) compared to leaves dried using the other tested methods (p<0.05). Additionally, microwave-dried P. bleo leaves displayed the highest DPPH inhibition (91.62%) and exhibited the most potent IC50 value (76.90 ± 1.06 μg/mL) compared to oven and shade-dried leaves (p<0.05). P. bleo leaves dried with a microwave also recorded a significantly higher FRAP value (62.66 ± 0.10 μg TE/g dry extract) than oven-dried leaves (p<0.05). In conclusion, microwave drying emerged to be an efficient drying method in preserving the colour and antioxidant properties of the P. bleo leaves, suggesting its potential as a favourable drying technique for retaining bioactive compounds in medicinal plant materials.